A Phenomenological Study of Students’ Problem-Solving Skills : A View from Cultural Background - Adi Dewantoro; Citra Tectona Suryawati; Alifiya Haura Pramonoputri; Diva Asri Agustin; Lokahita Narima Purnajati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to analyze students' problem-solving skills from the perspective of their cultural background. This research used a qualitative approach with a phenomenological method. Data were collected through interviews and verification of cultural background from identity cards, and analyzed following Moustaka's method. The research findings revealed that students had three main ways of approaching problem-solving. Firstly, university students chose solutions influenced by the cultural practices they embrace.  Secondly, university students selected solutions with assistance from close acquaintances while adhering to societal norms.  Lastly, university students  emphasized the importance of resolving issues thoroughly.